2012
DOI: 10.1002/pmic.201100609
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the bovine uterine and plasma proteome using iTRAQ proteomics

Abstract: Early embryo loss is a key factor affecting fertility in dairy and beef herds. Prior to implantation, the bovine embryo spends around 16 days free-floating in the uterine environment and is dependent on the composition of uterine fluid for normal growth and development. However, there is a lack of information regarding the protein composition of the bovine uterus and how it relates to plasma. In this study, uterine flushings (UF) (n = 6) and blood plasma (n = 4) were collected from beef heifers on day 7 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 79 publications
(95 reference statements)
4
30
0
Order By: Relevance
“…Embryos from chow-fed mothers were cultured from the two-cell stage [embryonic day (E) 1.5] to blastocyst stage (E3.5) in KSOM medium containing either 1 or 4 mg/ml bovine serum albumin (BSA) concentration before evaluating TE endocytosis activity using the fluid marker fluorescein isothiocyanate (FITC)-dextran in the same medium. BSA was chosen because albumin is the major protein found within uterine fluid (Velazquez et al, 2010;Faulkner et al, 2012). We found both the number and collective volume of FITC-dextran labelled vesicles within blastocyst TE to be increased after culture in 1 mg/ml BSA ( Fig.…”
Section: Induction and Regulation Of Blastocyst Te Response To Maternmentioning
confidence: 99%
“…Embryos from chow-fed mothers were cultured from the two-cell stage [embryonic day (E) 1.5] to blastocyst stage (E3.5) in KSOM medium containing either 1 or 4 mg/ml bovine serum albumin (BSA) concentration before evaluating TE endocytosis activity using the fluid marker fluorescein isothiocyanate (FITC)-dextran in the same medium. BSA was chosen because albumin is the major protein found within uterine fluid (Velazquez et al, 2010;Faulkner et al, 2012). We found both the number and collective volume of FITC-dextran labelled vesicles within blastocyst TE to be increased after culture in 1 mg/ml BSA ( Fig.…”
Section: Induction and Regulation Of Blastocyst Te Response To Maternmentioning
confidence: 99%
“…Some recent studies have described the protein content of ULF in cyclic heifers (Mullen et al 2012a(Mullen et al , 2012b, at a single timepoint either considerably before (day 7: Faulkner et al 2012) or after (day 18: Ledgard et al 2009) pregnancy recognition, or in non-physiological models involving the transfer of up to 50 embryos per recipient (day 7: Munoz et al 2012). This study provides new knowledge regarding the composition and quantitative changes in ULF during key morphological events in early pregnancy in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported plasma proteomics profiles in dairy cows determined by iTRAQ analysis [7,8]. To date, however, there were few proteomics studies aimed at investigating the effects of HS on the plasma proteomics in lactating dairy cows.…”
Section: Introductionmentioning
confidence: 99%